Barrier Lyapunov function based adaptive region tracking control for underwater vehicles with thruster saturation and dead zone. Issue 11 (July 2021) - Liu, Xing; Zhang, Mingjun; Yao, Feng; Yin, Baoji; Chen, Junwei
Highlights: Barrier Lyapunov function based adaptive region tracking control scheme is proposed. An extra loop about nonlinear error transformation is added in the region tracking control. A smooth function about control signals is reconstructed to replace the control input with thruster saturation and dead zone. An improved Nussbaum functions is designed to deal with the unknown control gain. Abstract: This paper proposes a new adaptive region tacking control scheme with nonlinear error transformation for underwater vehicles based on barrier Lyapunov functions. In the new scheme, a redefinition of the tracking error is given by introducing nonlinear error transformation in prescribed performance control. Although the results created by the new scheme indicate a slight decrease in the tracking precision, the real tracking error will be still kept within the prescribed performance functions, while the control signals also become smoother, compared with the original prescribed performance control scheme. Then an approximation form of the control input with constraints, together with an improved Nussbaum function, is designed to derive the control law for underwater vehicles with thruster saturation and dead zone. Furthermore, a new velocity error variable is given by introducing an auxiliary variable to compensate the effect from thruster saturation. Finally, it is proved that the nonlinear system is semi-global practical finite-time stable and the tracking error is always kept within the prescribed boundaries. The effectiveness of the proposed region tracking control scheme is validated through simulation-based case studies on an underwater vehicle with measurement noise.